2020
DOI: 10.1007/s12520-020-01059-5
|View full text |Cite
|
Sign up to set email alerts
|

Controlled experiments in lithic technology and function

Abstract: This article is part of the Topical Collection on Controlled experiments in lithic technology and function * João Marreiros

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…To isolate the effect of material hardness while maintaining reasonable costs and effort, we opted for a tightly controlled protocol [30,31]. Flint bits (Baltic/morainic flint from Denmark with nano-crystalline non-oriented chalcedony texture [25]) were rubbed against dry bone, antler, and wood (beechwood and spruce) using a tribometer at room temperature.…”
Section: Methods Experimental Setupmentioning
confidence: 99%
“…To isolate the effect of material hardness while maintaining reasonable costs and effort, we opted for a tightly controlled protocol [30,31]. Flint bits (Baltic/morainic flint from Denmark with nano-crystalline non-oriented chalcedony texture [25]) were rubbed against dry bone, antler, and wood (beechwood and spruce) using a tribometer at room temperature.…”
Section: Methods Experimental Setupmentioning
confidence: 99%
“…Microstructural characteristics are also thought to potentially affect the size and/or shape of a final knapped product [2]. This is supported by replicative experiments conducted by contemporary knappers which have demonstrated that higher quality raw material has a direct influence on the manufacturing process [8][9][10][11][12][13][14][15]. Some scholars argue that a good raw material that is suitable for knapping should be brittle, elastic, and isotropic [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Simple models allow for simple experimental designs that are more likely to yield “clean” interpretable results. In many ways, these models are similar to the kinds of controlled experiments that have become more common in lithic studies (Lin et al 2018; Marreiros et al 2020). Both emphasize variable control and manipulation so that the experimental outcomes can be attributed securely and causally to the experimental variables rather than confounded by “nuisance” factors (Lin et al 2018).…”
Section: Discussionmentioning
confidence: 92%